Ultraprecision tool-servo cutting of pure nickel for fabricating micro/nanostructure arrays. (September 2022) - Du, Hanheng; Jiang, Mengnan; Zhu, Zhiwei; Wang, Zuankai; To, Suet
Graphical abstract: Highlights: The ultraprecision tool-servo cutting process was proposed to generate the micro/nanostructure arrays on pure nickel surfaces. The micro-lens array was generated with high fabrication accuracy, demonstrating the effectiveness of the proposed cutting process. The sawtooth-shaped nanostructure array on an area of 13 mm × 14 mm was generated with high fabrication efficiency. Sawtooth-shaped nanostructure array triggers the generation of structural colors with high chromaticity and high brightness. Abstract: The fabrication of micro/nanostructure arrays on nickel or nickel alloy surfaces is still a challenge because of the high hardness and low thermal conductivity. Motivated by this, this study proposed the ultraprecision tool-servo cutting process to fabricate micro/nanostructure arrays on the nickel surfaces. Experimental results showed the micro-lens array and sawtooth-shaped nanostructure array were successfully fabricated on pure nickel surfaces. The fabrication error of the micro-lens array is<1.2%, demonstrating the high fabrication accuracy of the proposed cutting process. Furthermore, the sawtooth-shaped nanostructure array triggers the generation of different structural colors. The cyan, blue, yellow, and green with high chromaticity and high brightness were clearly observed on the pure nickel surface. The fabrication time of the sawtooth-shaped nanostructure array is 45 mins, demonstrating the high fabrication efficiency of the proposed cutting process. This study provides a flexible and highly efficient fabrication method to generate micro/nanostructure arrays, which could extend the application fields of nickel and its alloy to optics.